Impactos do novo ensino médio para a aprendizagem de matemática na perspectiva de estudantes finalistas da rede pública estadual de Manaus - Leite, Regina Pereira (Brasil, 2025)
This paper addresses the changes in basic education in Brazil, with an emphasis on high school and the recent reform introduced by Law No. 13,415/2017, known as the New High School. The reform proposes to modernize the school curriculum, increasing the workload and introducing training itineraries, which aim to bring education closer to the demands of the job market and contemporary society. However, the reform has generated several controversies, especially regarding the fragmentation of the curriculum and the comprehensive education of students. The objective is to analyze the consequences of the reform for high school, within the scope of the Mathematics discipline, exploring the tensions between curricular flexibility and the need for broad and critical education, which enables the comprehensive development of students. The research was conducted with a qualitative approach, using a bibliographic review and analysis of legal and educational documents. In addition, a field study was conducted in two public schools of the State High School Network in the city of Manaus, with questionnaires being administered to final year students to investigate their knowledge and perceptions about the reform and its impacts. The questions addressed topics studied during high school and perspectives on teaching for learning Mathematics. Analysis of the data obtained revealed that, although there is some knowledge about the reform, there are still many doubts and resistance, especially regarding the viability of full-time education and the adequacy of flexibility to meet students' needs. The research also highlighted that, while some educators see the reform as an opportunity to improve students’ professional training, others warn of the risk of more fragmented education, with less space for students’ critical and comprehensive training. Students, in turn, expressed concern about the lack of guidance on choosing training paths and the difficulties in reconciling the increased workload with their socioeconomic realities. Based on the theoretical framework, which includes authors such as Nosella (2015), Freire (2005), and Marx (2006), this work reflects on the contradictions between curricular flexibility and the need for broad, critical, and integrative training. The study proposes alternatives to improve the implementation of the reform, making high school more inclusive, effective, and aligned with the needs of society and young Brazilians.